Economical Analysis On Fishing Boats For Fishermen In The Coast Of Banyu Urip, Ujung Pangkah, Gresik - Mahasin Maulana Ahmad; Hermanto (Samakia : Jurnal Ilmu Perikanan, 2020)
Banyu urip is one of the many villages in the north sea of Gresik. The main livelihood of community is fisherman. To bring it to life, the fisherman need decent fishing boats that is suitable for their age. The fishing boats in Banyu urip are 6-8 years old on average. The fishing boat use fishing nets and gears, and the main catch is shellfish and some other fish. In a year, fisherman can sail up to 200 trips. To develop that potential, an economic analysis need to be done related to the benefits of fishing boats for fisherman around the Banyu urip. The purpose of this research is to find out the initial investment costs, the expenses in one trip, average income of fisherman in a year and payback period of the investment. This research was conducted in several stages, calculate ship procurement costs, operational cost in one trip and also variable cost, so that expenses and income can be known. The next step is analysis of profitability and investment payback period. Based on the results of analysis and calculation, the investment value of the ship is obtained, the price, equipment, and engine of ship are 70 million rupias. Expenses in a year, fuel cost, lubricating oil cost, provision fees, ship repair cost and also depreciation expense are 27,399,101 rupias. The income of fishing boats are 62,266,666 rupias/year with 13.37 % Internal Rate of Return and the payback period is 1.6 years. Key Words: Economical, Fisherman, Fish Boat, Banyu Urip